Analysis of Beef Marketing in Song Local Government Area of Adamawa State, Nigeria - Hamid, Hamid; Bello, Bello (International Journal of Humanities and Education Development (IJHED), 2020)
The study analyzed beef marketing in song local government area of Adamawa state Nigeria. Data for the study were primary generated from the respondents through structured questionnaire which spanned for six months (July, - December 2019). Descriptive statistics (frequency count and percentages) and Net Marketing Income (NMI) were used to analyzed the data. The results shows that beef marketing is dominated by males, middle aged, married, experienced and fairly educated people. It also shows that beef marketing is profitable, because, averagely beef marketers were generating N116.64 per kilogram of beef marketed and a marketing ratio of 0.35. This revealed that for any one naira invested in beef, marketers were making 35 kobo as profit. Identified problems affecting beef marketing in the area include credit recovery, sales on credit to bulk buyers and end users, poor access to credit, poor road network, high transportation cost, inadequate access to credit facilities, inadequate market information and in effective storage and preservation facilities which lead to beef spoilage and high risk of losses especially for unsold beef. The study concludes that, beef is marketed through simple but in effective channels in the area despite the fact that it is a profitable venture. The study therefore recommended that; rural –urban roads should be improved to minimize cost and ease movement of produce, credit facilities should be made available and affordable for beef marketers, to facilitate acquisition of storage/preservation and other modern marketing facilities.